Status and Potential for Food and Sago Baruk Conservation Land - ABNER LAY; CHANDRA INDRAWANTO (Perspektif, 2013)
The Arenga microcarpha (sago baruk) has a prospect to be developed because its food source as sago baruk flour and its side products such as cattle feed, wood and organic fertilizers, as well as its support for land conservation due to its ability to grow well in varying critical and long dry season areas which enables to control erosion and ground water. The optimal growth of sago baruk requires minimized trim which can be used as cattle food. Sago baruk farm management would be efficient if combination patter of Sagu  baruk, forestry plants and cattle could be applied in one are. The pattern would produce diversification products, such as sago baruk starch, beef cattle, organic fertilizers  and wood. The pattern will be implemented appropriately and intensively in sago baruk areas to provide more employment and opportunities, increase of income, and provide sustainable food for people. Key words: Arenga microcarpha,  sago baruk starch, cattle feed, land conservation